2008
DOI: 10.1681/asn.2007080895
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Renal Tubule Cell Therapy for Acute Renal Failure

Abstract: The mortality rate for patients with acute renal failure (ARF) remains unacceptably high. Although dialysis removes waste products and corrects fluid imbalance, it does not perform the absorptive, metabolic, endocrine, and immunologic functions of normal renal tubule cells. The renal tubule assist device (RAD) is composed of a conventional hemofilter lined by monolayers of renal cells. For testing whether short-term (up to 72 h) treatment with the RAD would improve survival in patients with ARF compared with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
146
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 194 publications
(149 citation statements)
references
References 20 publications
0
146
0
3
Order By: Relevance
“…A phase II, multicenter, randomized trial involving 58 patients with AKI and who had required continuous RRT (CRRT) demonstrated that, at 28 days, the mortality was 33% in the RAD group and 61% in the CRRT group. 34 The Kaplan-Meier analysis revealed that survival through day 180 was significantly improved in the RAD group, and the Cox proportional hazard model suggested that the risk for death was approximately 50% of that observed in the CRRT-alone group. Tumlin et al reported substantial improvement in patients' outcomes over standard-care therapy with the use of a selective cytophoretic device.…”
Section: Renal Cell Therapy and Bioartificialmentioning
confidence: 98%
“…A phase II, multicenter, randomized trial involving 58 patients with AKI and who had required continuous RRT (CRRT) demonstrated that, at 28 days, the mortality was 33% in the RAD group and 61% in the CRRT group. 34 The Kaplan-Meier analysis revealed that survival through day 180 was significantly improved in the RAD group, and the Cox proportional hazard model suggested that the risk for death was approximately 50% of that observed in the CRRT-alone group. Tumlin et al reported substantial improvement in patients' outcomes over standard-care therapy with the use of a selective cytophoretic device.…”
Section: Renal Cell Therapy and Bioartificialmentioning
confidence: 98%
“…− , and glucose, as well as the excretion of ammonia and normal levels of 1,25-OH-vitamin D3 [50]. Moreover, the RAD modulates systemic inflammation by regulating circulating levels of several cytokines.…”
Section: Convection-based High-volume Techniques (Hvhf)mentioning
confidence: 99%
“…150,155 This more "complete" renal replacement was felt to be safe 151 and to convey 180 day survival and return of renal function benefits to a small group of ICU patients enrolled in an open-label trial for CVVH with RAD augmentation. 156 Phase III trials have not been published but are planned according to the authors. However, the RAD is a long way from the criteria for ultimate renal replacement support, as it is used in conjunction with standard, machine-based hemofiltration whereby the ultrafiltrate is shuttled through the RAD with reclamation of approximately 25% of solute and fluid prior to return to the patient.…”
Section: Acknowledgementsmentioning
confidence: 99%